Pengembangan Media Pembelajaran tentang Tumbuhan Monokotil dan Dikotil Menggunakan Augmented Reality - Jozua F Palandi; Taufik Rachman; Fazar Arizal Fahmi (J-INTECH ( Journal of Information and Technology), 2022)
The development of technology in learning today has grown very rapidly and has become one of the basic human needs. Learning media is a device that is used to transmit information from the sender to the recipient which will stimulate thoughts, feelings, concerns, and interests that lead to a learning process. The use of Augmented Reality (AR), namely by inserting 3D virtual objects into the real environment in real-time, in this context, is the layer of dicot and monocot plants, with the aim of presenting them in a more real and attractive way. Thus, this learning media will provide freedom for students in carrying out the process of discovering knowledge in their own way. The development of this application uses the waterfall method, with the intention of working on the system to run sequentially to avoid repeating stages. This application runs on the Android mobile platform. Before creating a 3D object, it is necessary to register a marker with Vuforia so that the object can be accessed and displayed. After being registered in Vuforia and the 3D object in Blender is complete, then the object will appear above the marker. This application is expected to increase the interest of grade 4 elementary school students in learning Dicot and Monocot plants.